2002
DOI: 10.1063/1.1517716
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the activation energy in coupled CdTe/ZnTe quantum dots and quantum-well structures with a ZnTe thin separation barrier

Abstract: Temperature-dependent photoluminescence measurements showed that the activation energy of CdTe/ZnTe quantum dots (QDs) coupled with a quantum well is much larger than that of the QDs alone, This behavior is attributed to the tunneling of carriers via a thin separation layer from the quantum well to the QDs. The present observations can help improve understanding of the enhancement of the activation energy in coupled CdTe/ZnTe nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As a matter of fact, experimental studies on nanoparticles of 2−6 nm in diameter are becoming routine work. , The case of II−VI nanoparticles is not an exception. Binary compounds such as ZnO , and ZnS, , CdS, CdSe, and CdTe ,, and ternary compounds such as CdS/ZnS, CdSe/ZnSe, , CdTe/ZnTe, and CdSe/CdTe have recently been studied. These nanoparticles are grown in solution, where organic molecules surround the nanoparticle to stop its growth.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, experimental studies on nanoparticles of 2−6 nm in diameter are becoming routine work. , The case of II−VI nanoparticles is not an exception. Binary compounds such as ZnO , and ZnS, , CdS, CdSe, and CdTe ,, and ternary compounds such as CdS/ZnS, CdSe/ZnSe, , CdTe/ZnTe, and CdSe/CdTe have recently been studied. These nanoparticles are grown in solution, where organic molecules surround the nanoparticle to stop its growth.…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups have already reported observations of the photoluminescence (PL) from self-organized QDs of CdTe on ZnTe. [1][2][3][4][5] These QDs have been observed as dotlike islands by surface measurement. Kuroda et al observed a PL peak from the QDs grown by atomic layer epitaxy (ALE) at a substrate temperature of 300 C in a molecular beam epitaxy (MBE) chamber.…”
Section: Introductionmentioning
confidence: 96%
“…However, relatively little work has been performed on II-VI QDs in comparison with III-V QDs because of the delicate problems encountered in the growth process. Among these II-VI QDs, wide-gap CdTe QDs, because of their advantages of higher excitonic binding energies, are of great interest due to their potential applications in optoelectronic devices operating in the green spectral range [12,13]. The control of the QDs size, shape, and size distribution is of great interest for the fabrication of QDs devices and investigation of their physical properties.…”
Section: Introductionmentioning
confidence: 99%